The Contribution of Mutualist Associations Towards a New European Bauhaus (EAAE Annual Conference Proceedings, 2023)
The aim of this paper is to discuss how mutualist associations (MA) in Portugal can contribute for the sustainability of communities and territories, namely in terms of health, well-being and welfare of the communities and territories resilience, in alignment with sustainable development goals number 3, 11 and 17 from a multi and transdisciplinarity.